Cardiovascular outcomes in women with the highest classification of maternal cardiovascular risk in pregnancy. (14th October 2021) - Nashat, H; Rocha, L; Constantine, A; Pires, A; Patel, R; Swan, L; Alexander, D; Gatzoulis, M A; Johnson, M; Dimopoulos, K; Rafiq, I
Abstract: Introduction: The modified world health organization (mWHO) classification of maternal risk is used to estimate morbidity and mortality in pregnant women with cardiovascular disease. Those in the highest risk category (mWHO Risk Class IV) are at greatest risk. Pregnancy is contraindicated in this patients. Methods: This was a retrospective review of pregnant women classified as mWHO risk class IV, who were managed in a tertiary joint cardiac-obstetric pathway between 2008 and 2018. Results: In total, there were 35 pregnancies in 30 women with the highest cardiovascular risk for adverse maternal outcomes. The mean maternal age at delivery was 29.3±5.2 years. Eleven (36%) patients were diagnosed with cardiovascular disease during pregnancy. Fourteen had a form of pulmonary arterial hypertension (46%), 6 (20%) had severe systemic ventricular dysfunction, 4 (13%) had severe mitral or aortic stenosis, 4 (13%) had aortic dilatation or inherited aortopathy, 1 (3%) had a history of peri-partum cardiomyopathy and 1 (3%) had severe native coarctation of the aorta. In the 30 pregnancies followed up in our centre, 29 (96%) were single foetus pregnancies and 1 (4%) was a twin pregnancy. There were 30 live births, 1 foetus was lost in the twin pregnancy. Of these 29 (96%) patients underwent elective caesarean section and 1 (4%) emergency caesarean section. Cardiovascular complications occurred in 18 (60%) women. Of these, 5 (28%) had atrial arrhythmias during pregnancy, 6 (33%) had worsening of pulmonary hypertension, 6 (33%) had decompensated heart failure. Three women had interventions during pregnancy: 1 had percutaneous intervention for coarctation of aorta due to foetal and maternal compromise, 1 had electrophysiological ablation for atrial arrhythmias to improve systemic ventricular function and 1 had an electrical cardioversion for atrial fibrillation. There were no deaths during pregnancy or in the peripartum period. One patient who presented at 34 weeks gestation with severe peripartum cardiomyopathy required early inotropic support followed by extracorporeal membrane oxygenation (ECMO) support post-delivery, died at 2 months post-partum. Conclusions: With appropriate pre-pregnancy optimization, antepartum surveillance individualised peripartum care plans and multidisciplinary care throughout pregnancy, women at the highest risk for cardiovascular outcomes can have successful pregnancies, although the risk of cardiovascular complications remains high. Funding Acknowledgement: Type of funding sources: None.